Pengaruh Literasi Keuangan dan Gaya Hidup Gen Z terhadap Perencanaan Keuangan - Dahniyar Daud; Muh. Raswal Zulfitra; Ferdi Gogo Mendaun; Muh. Zulfikar Zaky Eppe (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
Financial planning is the process of evaluating and managing finances systematically and planfully to achieve short-term, medium-term, and long-term financial goals. This process involves arranging income, expenditures, investments, and managing financial risks with the aim of ensuring stability and meeting future financial needs. This study aims to analyze Financial Planning used to explain the influence of independent variables such as Financial Literacy and Lifestyle (A Study on Gen Z in Makassar City). The data collection in this study uses primary data obtained from findings collected through the distribution of questionnaires to Gen Z in Makassar City using Non-Probability Sampling Technique, specifically Purposive Sampling Technique. The population in this study is Gen Z located in Makassar city aged 20 to 29 years with a total of 249,969 individuals. This data is obtained from the Central Statistics Agency of Makassar (BPS). The sample taken for this study was 100 samples. The results of this study show that the Financial Literacy variable has a significant positive effect on Financial Planning, and Lifestyle has a significant positive effect on Financial Planning.